3,5-Dimethoxy-4′-methylbiphenyl - Lahtinen, Manu (International Union of Crystallography, 2013)
The title compound, C(15)H(16)O(2), crystallizes with three independent molecules in the asymmetric unit. The intramolecular torsion angle between the aromatic rings of each molecule are −36.4 (3), 41.3 (3) and −37.8 (3)°. In the crystal, the complicated packing of the molecules forms wave-like layers along the b and c axes. The molecules are connected via extensive methoxy–phenyl C—H⋯π interactions. A weak C—H⋯O hydrogen-bonding network also exists between methoxy O atoms and aromatic or methoxy H atoms.